Analysis of Variations in Tub Cover Tarpaulin Shape against Airflow Patterns and Pressure Distribution Characteristics on Pickup Trucks with the Addition of Roof Deflector - Aditya Mulyawan; Anak Agung Adhi Suryawan; Ainul Ghurri (HM Publisher, 2022)
This study aimed to analyze the airflow pattern and pressure distribution characteristics of a pickup truck with a roof deflector added. with an angle of curvature of 20° and is accompanied by the installation of a tarpaulin cover on the body of the pickup truck. The method used in this study is an experimental method by testing 6 specimens, namely a pickup truck added with a roof deflector without using a tarp or baseline, a pickup truck added with a roof deflector fitted with a tonneau cover tarp (type A), aerocap tarpaulin with an angle of 0° (type B). and 12° (type C), and cincing type tarpaulin with a foot angle of 15° (type D) and 30° (type E) in a wind tunnel with a speed of 5.47 m/s. The more aerodynamic the use of tarpaulin, the more the blockage mass will be reduced so that it can produce a streamlined flow pattern. The results showed that the pickup truck added with a roof deflector with a 15° cincing tarp had a stable Cp value fluctuation at the rear of the pickup truck, while the pickup truck added a roof deflector with a 12° aerocap tarp. as well as produce aerodynamic flow thereby reducing the occurrence of blockage mass and obstacles.